KARAKTERISTIK AKSEPTOR INTRA UTERINE DEVICES (IUD) DI KECAMATAN PURWOKERTO TIMUR KABUPATEN BANYUMAS TAHUN 2013 - Ema Wahyuningrum; Sindhy Desitavani (Universitas Harapan Bangsa Purwokerto, 2013)
IUD is a long-term contraceptives with low side effects but demand is still lessthan the syringe and pills. In Banyumas with EFA number as many as 1,752,846people only 27 149 votes (11.12%) who use IUD. Based on the pre-survey, in2013 the most IUD acceptors in District Purwokerto, Banyumas Regency East anumber of 1624 votes (24.06%).The purpose of this study to investigate thecharacteristics of IUD acceptors in District Purwokerto, Banyumas Regency Eastin 2013 based on education, occupation, age, and socio-economics.This study was descriptive quantitative method with cross sectional approach.This study uses secondary data. The population in this study were all IUDacceptors in the subdistrict of East Purwokerto, Banyumas regency in 2013 whichamounted to 1,624 people. Sampling in this study using a quota sample with asample of 163 acceptors.From the results, the acceptor who choose IUDcontraception is women who are highly educated, working, aged> 35 years andhave a good social economy. Keywords: Characteristics, Acceptors, Intra Uterine Devices